Molecular Alterations in Solid Pseudopapillary Neoplasm of the Pancreas: The Achilles Heel in Conquering Pancreatic Tumorigenesis. Issue 10 (November 2021) - Ghio, Michael; Vijay, Adarsh
Abstract: Solid pseudopapillary neoplasms of the pancreas are overwhelmingly benign tumors predominately observed in women in the third decade of life. However, their malignant potential, based on local recurrences and metastases, has brought into question the available evidence on their biological behavior. Solid pseudopapillary neoplasms have distanced themselves from other pancreatic tumors with varying morphological appearance, immune profile, and histogenesis. In review of the literature, PubMed was queried using search strings, including "solid pseudopapillary neoplasm" and "molecular, " and "immunohistochemistry." Alternative searches were also conducted given the variability in tumor name, including "solid pseudopapillary tumor" and "Frantz tumor." This article provides an in-depth review into the molecular pathways that contribute to the pathogenesis of solid pseudopapillary neoplasms. It also discusses the implications of existing molecular pathways toward tumor aggressiveness and recurrence potential.